Relevansi Kewibawaan dan Kewiyataan dengan Hasil Belajar Siswa - Abdillah, Abdillah (Nadwa, 2012)
This paper elaborates student echivement based on authority, education, and quality of studentsâ learning. The study shows that the relationship between au-thority, education, and quality of studentsâ learning activity toward learning result in middle school category is bigger than high or low school category. The quality of studentsâ learning activity is oppointed by authority and education implemented by the teachers in learning process. The authority, education, and quality of studentsâ learning have relation significantly to the student echive-ment. The relationship of authority, education, and quality of studentsâ learning is definitly difference in predicting their echivement. Trough authority and edu-cation in learning process, the studentâs echivement can be increased.